2015
DOI: 10.3928/01477447-20150305-51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Manipulation on Range of Motion in Patients With Stiff Total Knee Arthroplasty

Abstract: Although manipulation under anesthesia (MUA) has been considered effective first-line treatment for stiff total knee arthroplasty (TKA), there is no consensus regarding the usefulness of repeated MUA. The purpose of this study was to investigate the usefulness of repeated MUA performed for patients in whom satisfactory range of motion (ROM) was not achieved by MUA. The authors retrospectively reviewed 15 patients who underwent repeated MUA after failure of initial MUA for stiff TKA. Demographic and ROM data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…7,28 Repeat manipulations have demonstrated success in some studies with improvements in knee ROM of 17-29 degrees. [29][30][31] Nineteen patients (10%) in this study underwent a repeat MUA, and a significant increase in risk of revision was found with each subsequent MUA. Patients who underwent three or more MUAs had a relative risk of 27.02 for revision.…”
Section: Discussionmentioning
confidence: 92%
“…7,28 Repeat manipulations have demonstrated success in some studies with improvements in knee ROM of 17-29 degrees. [29][30][31] Nineteen patients (10%) in this study underwent a repeat MUA, and a significant increase in risk of revision was found with each subsequent MUA. Patients who underwent three or more MUAs had a relative risk of 27.02 for revision.…”
Section: Discussionmentioning
confidence: 92%
“…The definition(s) of "arthrofibrosis," "stiffness," and/or "flexion contracture" utilized as inclusion criteria in each study were assessed. Of the 35 studies included in our review, 2 used the clinical term "arthrofibrosis," 20,41 29 used "stiffness," 1,12,[16][17][18][19][20][28][29][30][31][32][33][34][35][38][39][40][41][42][43][44][45][46][47][48][49][50][51] and 11 used "flexion contracture." 4,16,20,[36][37][38][50][51][52][53][54] Five studies used a combination of the aforementioned clinical terminology as inclusion criteria 16,20,38,41,51 .…”
Section: Clinical Definitionsmentioning
confidence: 99%
“…4,16,20,[36][37][38][50][51][52][53][54] Five studies used a combination of the aforementioned clinical terminology as inclusion criteria 16,20,38,41,51 . For 12 studies 12,18,19,28,29,33,35,[44][45][46][47][48] that did not explicitly define inclusion criteria, but instead listed rangeof-motion criteria for manipulation under anesthesia, definitive criteria for manipulation under anesthesia were used as surrogate definitions.…”
Section: Clinical Definitionsmentioning
confidence: 99%
“…However at week 6 the mean function sub-score results were better in the CPM group than the MUA group (p ​= ​0.065). Other research has shown substantial decreases in ROM following MUA over time with some requiring repeat MUA or further surgery [ [44] , [45] , [46] , [47] , [48] , [49] ]. This initial gain then deterioration in ROM may be explained by an abnormal inflammatory response caused or exacerbated by the sudden breakdown of scar tissue, lack of physiotherapy and or the opportunity to complete stretching exercises independently at home.…”
Section: Study Resultsmentioning
confidence: 99%